Troponin I, Hyperlipidemia and Obesity as Predictor of Cardiovascular Complications: A Cross Sectional Study: Troponin I and Cardiovascular Complications - Haq, Zainab; Zaidi, Syed Usama Shayan; Shahid, Muhammad Nauman; Munir, Maria; Butt, Tahreem Waheed; Yousuf, Nawal; Shahbaz, Muhammad Nasir (Pakistan Journal of Health Sciences, 2024)
High levels of Troponin I, cholesterol, triglycerides, Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL) and Body Mass Index (BMI) are predictor of cardiac complications. Objective: To investigate the predictive efficacy of Troponin I, BMI, and lipid profiles in detecting cardiovascular problems. Methods: 300 male and female individuals were selected for current study. 100 normal individuals were in Control Group A, while 100 participants were placed in Group B all the individuals of Group B have the indications of different cardiac medical complications. BMI, systolic, diastolic blood pressure, Troponin I, cholesterol, triglycerides, LDL, HDL levels were measured respectively. Results: In present study BMI, systolic blood pressure, diastolic blood pressure, Troponin I, cholesterol, triglycerides, LDL, HDL blood serum levels of male and female in Group A and Group B were measured, the comparative analysis of above biomarkers showed a significant p-Value ≤ 0.05 change (0.02 ± 0.01, 183.01 ± 0.02, 120.01 ± 0.02, 87.01 ± 0.03, 44.01 ± 0.01), (0.02 ± 0.01, 172.01 ± 0.02, 130.01 ± 0.01, 88.01 ± 0.03, 42.01 ± 0.04), (0.39 ± 0.04, 272.01 ± 0.02, 180.01 ± 0.01, 138.01 ± 0.03, 37.01 ± 0.01) and ( 0.37 ± 0.04, 282.01 ± 0.02, 184.01 ± 0.01, 141.01 ± 0.03, 36.01 ± 0.01) were measured respectively. Conclusions: The present study found that there were notable significant p-value <0.05 differences in the blood serum levels of BMI, systolic and diastolic blood pressure, Troponin I, cholesterol, triglycerides, LDL, and HDL in both the male and female groups in Groups A and B